VISUALIZATION OF MOVEMENT IN GYMNASTICS EXERCISES - Iliya Kyuchukov (Scientific Publishing House. NSA Press, 2023)
Visualization of the movement is crucial both for research and pedagogical activities. The aim of this study was to introduce some methodology for the visualization of the movement on the basis of the data obtained from conducting numerical experiments when studying various movements and exercises. The main task was to design a program module for the visualization of spatial movements. The visualization of the results from the conducted simulations allows for having an idea of the studied movement in the course of solving the equations of motion. The program module for the visualization of an athlete's movement is working in the MATLAB Computing Environment. We have constructed an anthropomorphic structure (model) which resembles the shape of a human body. The model possesses a high degree of mobility which makes it suitable for applying various movements and actions. A set of artistic gymnastics exercises was provided as an example. The visualization of the current results from the simulated movement contributes to the detailed analysis and facilitates the interpretation of the obtained results. The model can also be applied to research activities for movements in other sports.